Astrocytic Sonic Hedgehog Alleviates Intracerebral Hemorrhagic Brain Injury via Modulation of Blood-Brain Barrier Integrity - Xing, Gebeili; Zhao, Tianman; Zhang, Xiyue; Li, He; Li, Xiuping; Cui, Pan; Li, Minshu; Li, Daojing; Zhang, Nan; Jiang, Wei (Frontiers in Cellular Neuroscience, 2020)
Background: Intracerebral hemorrhage (ICH) is a fatal subtype of stroke that lacks effective therapy. Blood brain barrier (BBB) damage is a hallmark of ICH-induced brain injury that leads to edema formation, leukocytes infiltration, influx of blood components into the perihematomal region, and eventually brain injury. Astrocytes are essential for the formation and maintenance of the BBB by providing secreted molecules that contribute to the association between these cells. Sonic hedgehog (SHH) derived from astrocytes promotes the maturity and integrity of the BBB by upregulating tight junctions (TJs) in brain capillary endothelial cells (ECs). However, the effect of SHH on BBB in ICH has not been investigated. Methods: Cyclopamine (CYC) is a potent, selective inhibitor that specifically blocks the SHH signaling pathway. Here, we used pharmacological inhibitions (CYC and its derivatives) to determine a critical role of the SHH signaling pathway in promoting BBB integrity after ICH by mechanisms of regulating the TJ proteins in vivo and in vitro. Results: The expression of astrocytic SHH was upregulated in mouse brains after ICH. Compared with the vehicle-treated group, inhibition of the SHH signaling pathway with CYC treatment and its derivatives aggravated neurological function deficits, brain edema, hematoma volume and BBB impairment by downregulating TJs in ECs through the SHH-Gli-1 axis in vivo and in vitro. Conclusions: SHH signaling pathway at the level of the BBB provides a barrier-promoting effect, suggesting that the SHH signaling pathway may function as a potential therapeutic target for restoring BBB function in ICH.